SAT0389 Validation of the Spanish Version of the Fibromyalgia Rapid Screening Tool (First). (23rd January 2014) - Torres, X.; Collado, A.; Gomez, E.; Arias, A.; Cabrera-Villalba, S.; Messina, O. D.; Vidal, L. F.; Clark, P.; Ríos, C.; Salomón, P. A.
Abstract : Background: Fibromyalgia syndrome (FM) requires an expert clinical examination that impedes an easy assessment of diagnostic criteria in some health settings. This problem delays its diagnostic, treatment and referral to specialized services 1, 2 . To solve this drawback, a new screening test, the Fibromyalgia Rapid Screening Tool (FiRST) was created 3 . Despite showing acceptable psychometric properties, notably independent of depression, anxiety, catastrophizing and functional disability, the validation of the FiRST has been questioned for including non-challenging comparators and excluding patients with a severe depression 4 . Objectives: To validate a Spanish version of the FiRST including pain disorders more analogous to fibromyalgia Methods: The FiRST was translated following international standards. Internal consistency and temporal stability were assessed. The ability of the FiRST global score as a screening tool for fibromyalgia (discriminant validity) was assessed by logistic regression analysis. To assess to what degree potential confounders might affect the discriminant validity of the FiRST (divergent validity), it was re-assessed by hierarchical multivariate logistic regression with demographics in a first step, followed by pain, anxiety and depression, catastrophizing, disability, and the FiRST global score in a last step. Results: The final sample comprised 257 patients (67% cases of fibromyalgia). The Spanish version of the FiRST showed acceptable internal consistency, reliability, and discriminant validity. The FiRST was able to discriminate between fibromyalgia and non-fibromyalgia patients even after discarding the effect of potential confounders. Both discriminant and divergent validity were, however, challenged by a moderate specificity (55% of non-fibromyalgia patients correctly classified). Conclusions: The Spanish version of the FiRST may be used as a screening tool for fibromyalgia even in those patients that present with psychopathology, a cognitive style characterized by catastrophizing about pain and high levels of functional disability. The moderate specificity of the Spanish version of the FiRST suggests that, in its current form, it must be better used to rule in a fibromyalgia rather than to rule it out. References: Annemans L, Wessely S, Spaepen E, Caekelbergh K, Caubere JP, Le Lay K et al. Health economic consequences related to the diagnosis of fibromyalgia syndrome. Arthritis Rheum 2008; 58(3):895-902. Choy E, Perrot S, Leon T, Kaplan J, Petersel D, Ginovker A et al. A patient survey of the impact of fibromyalgia and the journey to diagnosis. BMC Health Serv Res 2010; 10:102. Perrot S, Bouhassira D, Fermanian J. Development and validation of the Fibromyalgia Rapid Screening Tool (FiRST). Pain 2010; 150(2):250-256. Hansson PT. Yet another questionnaire is born! Pain 2010; 150(2):219. Disclosure of Interest: None Declared